Film studies - Buckland, Warren (Holder Stoughton Ltd., 1998)
Chapter 1: Film aesthetics: formalism and realism.- Chapter 2: Film structure: narrative and narration.- Chapter 3: Film authorship: the director as auteur.- Chapter 4: Film genres: defining the typical film.- Chapter 5: The non-fiction film: five types of documentary.- Chapter 6: The reception of film: the art and profession of film viewing
Keywords: Cine